Ethnocultural Influences on Women's Experiences of and Responses to Intimate Partner Violence, Los Angeles and Orange Counties, California, United States, 2014-2017 - Mechanic, Mindy Beth ([Verlag nicht ermittelbar], 2021)
Research about ethnocultural influences on women's experience of and response to intimate partner violence (IPV) is scarce, contributing to culturally incongruent processes that may deter some survivors from engaging with community systems. To fill this gap in the literature, this project examined the ways that cultural beliefs and contexts serve as a lens through which European-American, Mexican-American, Korean-American, and Vietnamese-American women experience and respond to IPV in their lives. Community-based recruitment techniques were used to recruit female survivors of intimate partner violence from the four target ethnic groups. Data collection included qualitative interviews (n = 112) and online surveys (n = 193) with survivors of intimate partner violence as well as focus groups with service providers (n = 37). While there were many shared experiences across survivors from the four ethnic groups, important differences in survivors' interpretation of abuse, strategies for managing the abuse, and help-seeking experiences did emerge. These differences have important implications for the development of culturally competent prevention and intervention strategies for survivors from different ethnic groups. This collection only contains the online survey data. The focus group and individual interview data will be released at a future date.